Impact of heritable disorders of connective tissue on daily life of children: Parent perspectives. (26th November 2020) - Wesley, Alison; Bray, Paula; Munns, Craig F; Pacey, Verity
Abstract : Aim: The aim of this study was to investigate parent perspectives on how heritable disorders of connective tissue (HDCT) affect a child's everyday life. In addition, this study aimed to determine if parents seeking health professional services perceive their children with HDCT to have difficulties with activities reliant on hand function. Methods: This cross‐sectional study used a questionnaire for parents to explore the impact of an HDCT on a child's ability to carry out everyday activities. Parents of children (8–18 years) attending a tertiary connective tissue dysplasia clinic, over a 12‐month period, were invited to participate. Results: We analysed 100 surveys completed by parents. Children with Ehlers–Danlos syndrome‐hypermobile type, joint hypermobility syndrome (48%) and osteogenesis imperfecta (42%) were the largest diagnostic groups represented. Pain (73%) and fatigue (68%) were the most common symptoms parents perceived to affect day‐to‐day activities. More parents were satisfied with their child's self‐care (61%) than school participation (33%). Keeping up with handwriting (71%) and gross motor activities (70%) were the most frequently reported difficulties at school. Most parents (65%) reported leisure activity difficulties, with pain (64%) and fatigue (60%) as the main contributing factors. Conclusions: This study has provided new knowledge about the concerns of parents with their child's engagement in everyday life including the impact of HDCT on hand function. Further research is needed on effective management strategies to reduce symptoms and improve hand function for these children.